Supporting Environmental Resilience through Biological Approach: Initial Step for Building Robusta Coffee Germplasm Database - Rustiati, Elly Lestari; Priyambodo, Priyambodo; Pratiwi, Dian Neli; Srihanto, Eko Agus; Lestari, Septi Wahyu; Sandra, Shifa; Winarno, Winarno; Thesalonika, Natasya (Bioma : Berkala Ilmiah Biologi, 2024)
In response to environmental challenges and the critical imperative for sustainable progress, rural regions including agriculture practices are important in ecological robustness. It can be achieved through a synergistic relationship between rural development sustainability and the biological sciences. Concurrently, research in stewardship approaches are underway to amass data on robusta coffee, Coffea canephora, species. In collaboration with Lampung Disease Investigation Centre and local coffee farmers in Pesawaran, Lampung, and under DIPA BLU Universitas Lampung year 2024, initial ongoing work on coffee germ plasm data is done. Robusta coffee leaves were sampled from 2 blocks of traditional coffee plantations, Wiyono and Bogorejo, Pesawaran, Lampung.  Of 18 robusta leaves’ samples DNA extraction, electrophoresis showed 14 samples with good results. The optimum temperature for amplification is 62 °C and 63 °C.  The results will be sequenced for its species confirmation.  This project is expected to contribute bottom up towards inclusive and sustainable rural futures at the local level.